Customer Loyalty of Inpatients of RSU Mardi Lestari Sragen in Review of Aspects of Hospital Image and Service Quality - Sulistiyaningrom, Woro; Isa, Muzakar; Wujoso, Hari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: In the context of Indonesia's health service organizations, which face increasingly fierce global competition, this study aims to examine the impact of hospital image and service quality on customer loyalty. Additionally, it aims to analyze the influence of hospital image on customer loyalty, with customer satisfaction as a mediating variable. Methodology: Quantitative methods are employed in this study, utilizing non-probability sampling with a purposive sampling technique. Data is collected through the distribution of questionnaires employing a Likert scale. The study population consists of inpatients at RSU Mardi Lestari Sragen, with 110 respondents. Data analysis is conducted using Partial Least Square (PLS) via SMARTPLS software, encompassing Outer and Inner model analyses. Results: The findings of this study indicate that hospital image and service quality positively and significantly influence customer loyalty. Moreover, customer satisfaction is a mediating factor in the relationship between hospital image, service quality, and customer loyalty. Applications: This research suggests that hospital management should strive to enhance its image by delivering exemplary services and ensuring patient satisfaction. Furthermore, the findings recommend bolstering the hospital's brand image and service quality to enhance patient satisfaction.